Effects of Leontice Smirnowii Tuber Monodesmosides and Crude Extract in Carrageenan- and Histamine-Induced Acute Inflammation Model of Rats - Gepdíremen, A.; Mshvildadze, V.; Bakuridze, K.; Elias, R. (Elsevier GmbH, Urban & Fischer Verlag, 2006)
Leontice smirnowii is a member of the Berberidaceae family. We have recently reported the 1,1-diphenyl-2-picryl-hydrazyl radical scavenging, superoxide anion radical scavenging, hydrogen peroxide scavenging, reducing power and metal chelating activities of L. smirnowii products. In the current study we investigated the possible effects of the crude extracts of L. smirnowii (CELS) and the monodesmoside's purified extract (MPE) of L. smirnowii in the carrageenan- and histamine-induced acute inflammation models in rats. The experiment revealed that CELS and MPE have anti-inflammatory effects, dose dependently in carrageenan-induced acute inflammation. On the other hand, their proinflammatory effects were surprisingly observed, especially in low doses, in the histamine-induced acute inflammation model. Summarizing these data, we may state that CELS and MPE exert their anti-inflammatory effects via non-histaminergic pathways. © 2005 Elsevier GmbH. All rights reserved.
Keywords: Berberidaceae; Carrageenan; Histamine; Inflammation; Leontice smirnowii; Monodesmosides